2022
DOI: 10.18521/ktd.990762
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education with Simulated Patient on the Empathy Attitudes of Medical Students: An Intervention Study

Abstract: Objective: In this study, it was aimed to investigate the effect of simulated patient and education on the empathy levels of third-year students in medical school. Methods: The study was carried out with 269 volunteer students. As a data collection tool, a short information form and the Jefferson Empathy Scale-Student Form were used. The scale was applied twice before and after the interview. Paired t test and Wilcoxan test were used for comparisons between the two groups. Results: The average age of the stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Empathy was briefly mentioned by the interviewees as one of the themes of the outcome of the interventions. Four studies did not mention how long the interventions were and when they were implemented 47–49,81 . Hence, we are not able to make a fair judgement whether the outcome (no significant change) was due to the duration.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Empathy was briefly mentioned by the interviewees as one of the themes of the outcome of the interventions. Four studies did not mention how long the interventions were and when they were implemented 47–49,81 . Hence, we are not able to make a fair judgement whether the outcome (no significant change) was due to the duration.…”
Section: Resultsmentioning
confidence: 92%
“…Upon further scrutiny, we found that different interventions were being implemented either as a one‐off intervention or over a span of time (refer to Table 1). There were four articles which did not mention the duration of implementation 47–49,81 . Of these four articles, the results showed no significant change in empathy for two quantitative articles 47,48 and the other two were qualitative research 49,81 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations